Society for Obstetric Anesthesia and Perinatology: Consensus Statement and Recommendations for Enhanced Recovery After Cesarean. (14th April 2021) - Bollag, Laurent; Lim, Grace; Sultan, Pervez; Habib, Ashraf S.; Landau, Ruth; Zakowski, Mark; Tiouririne, Mohamed; Bhambhani, Sumita; Carvalho, Brendan
Abstract : The purpose of this article is to provide a summary of the Enhanced Recovery After Cesarean delivery (ERAC) protocol written by a Society for Obstetric Anesthesia and Perinatology (SOAP) committee and approved by the SOAP Board of Directors in May 2019. The goal of the consensus statement is to provide both practical and where available, evidence-based recommendations regarding ERAC. These recommendations focus on optimizing maternal recovery, maternal-infant bonding, and perioperative outcomes after cesarean delivery. They also incorporate management strategies for this patient cohort, including recommendations from existing guidelines issued by professional organizations such as the American College of Obstetricians and Gynecologists and the American Society of Anesthesiologists. This consensus statement focuses on anesthesia-related and perioperative components of an enhanced recovery pathway for cesarean delivery and provides the level of evidence for each recommendation.